2003
DOI: 10.1104/pp.102.018986
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Analysis of the Rice Mitochondrial Proteome

Abstract: Purified rice (Oryza sativa) mitochondrial proteins have been arrayed by isoelectric focusing/polyacrylamide gel electrophoresis (PAGE), by blue-native (BN) PAGE, and by reverse-phase high-performance liquid chromatography (LC) separation (LC-mass spectrometry [MS]). From these protein arrays, we have identified a range of rice mitochondrial proteins, including hydrophilic/hydrophobic proteins (grand average of hydropathicity ϭ Ϫ1.27 to ϩ0.84), highly basic and acid proteins (isoelectric point ϭ 4.0-12.5), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
134
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(139 citation statements)
references
References 43 publications
4
134
0
1
Order By: Relevance
“…Batches of 200 g of rice (Oryza sativa 'Amaroo') seeds were washed in 1% (w/v) bleach for 10 min, rinsed in distilled water, grown in the dark in vermiculite trays (30 3 40 cm) at a constant 30°C, and watered daily, and the shoots were harvested at 10 d for mitochondrial isolation (Heazlewood et al, 2003). Rice shoots were harvested using scissors and cut into 5-to 10-mm lengths into a beaker on ice.…”
Section: Growth Of Rice Seedlings and Mitochondrial Preparationmentioning
confidence: 99%
“…Batches of 200 g of rice (Oryza sativa 'Amaroo') seeds were washed in 1% (w/v) bleach for 10 min, rinsed in distilled water, grown in the dark in vermiculite trays (30 3 40 cm) at a constant 30°C, and watered daily, and the shoots were harvested at 10 d for mitochondrial isolation (Heazlewood et al, 2003). Rice shoots were harvested using scissors and cut into 5-to 10-mm lengths into a beaker on ice.…”
Section: Growth Of Rice Seedlings and Mitochondrial Preparationmentioning
confidence: 99%
“…Further, the much reduced state of mitochondria in anoxia in yeast suggest an oxygen-derived trigger for full mitochondrial biogenesis, but the nature of mitochondrial proteomes under anoxia have not been systematically investigated to date in either anoxia-tolerant or -intolerant plants. We have recently studied the rice mitochondrial proteome in air-grown seedlings (25). By following the induction of respiration in rice coleoptiles during air adaptation of anoxic seedlings and assessing the changes in the rice mitochondrial proteome during this transition, we showed that much of the mitochondrial proteome appears relatively unaffected by anaerobic growth.…”
mentioning
confidence: 99%
“…In total, 136 nonredundant rice proteins were identified, including a new set of 23 proteins of unknown function located in plant mitochondria. Heazlewood et al [67] also reported the first direct identification, to our knowledge, of pentatricopeptide repeat proteins in the plant mitochondrial proteome. This dataset provides the first extensive picture of mitochondrial functions in a model monocot plant.…”
Section: Blue-native Pagementioning
confidence: 93%
“…This technique allows the separation in two dimensions of extremely hydrophobic protein sets and provides information on their native interactions [65]. Heazlewood et al (2003) reported rice mitochondrial proteome analysis using BN-PAGE. Purified rice mitochondrial proteins have been arrayed by IEF-PAGE, by BN-PAGE, and by RP HPLC separation.…”
Section: Blue-native Pagementioning
confidence: 99%
See 1 more Smart Citation